1984
DOI: 10.1063/1.333399
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional transmission electron microscopy study of silicide growth kinetics in the Cr/(100)Si system at 425 °C

Abstract: Cross-sectional transmission electron microscopy was used to determine the growth kinetics of silicide films in the Cr/(100)Si system. Growth rate, growth mechanisms, and structural details were obtained from direct observation of the reacted layer after various time intervals. At 425 °C, CrSi2 was the only phase formed; its growth was diffusion-limited, with a rate constant of 6.2×10−13 cm2/s. A thin oxide layer (∼20 Å) at the Cr/Si interface did not prevent silicide growth at 425 °C, but it served as an immo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…From the results, we see that Lϭ0. 15 and C 0 ϭ0.3 wt % are a pair of the better-fitted values to the experimental data for intermetallic compound growth at 200°C. Although the experimental data have some deviation from the t 1/3 growth, the agreement seems reasonable.…”
Section: B Comparison Of Model With Experimental Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the results, we see that Lϭ0. 15 and C 0 ϭ0.3 wt % are a pair of the better-fitted values to the experimental data for intermetallic compound growth at 200°C. Although the experimental data have some deviation from the t 1/3 growth, the agreement seems reasonable.…”
Section: B Comparison Of Model With Experimental Resultsmentioning
confidence: 99%
“…From the results of calculation, the model is better fitted to the experimental data when Lϭ0. 15 and C 0 ϭ0.3 wt % for compound growth at 200°C. The activation energy for Cu consumption in the soldering reaction was determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Natan et al [16,171 found that a parabolic (i.e. diffusions-limited) plot of film thickness versus annealing time fits their data much better than a linear (i.e.…”
Section: Growth and Structure Of Crsi Layersmentioning
confidence: 97%
“…Whereas in [16,171 and in our studies the layers were deposited by sputtering, in [18 to 211 the Cr films were e-beam evaporated. An annealing at 450 "C for 30 min results in 270 nm CrSi, layer thickness for sputtered films, but typically only about 140 nm for e-beam evaporation.…”
Section: Growth and Structure Of Crsi Layersmentioning
confidence: 99%